Voltammetric determination of the antioxidant concentrotion at the electrode of carbon nanotubes - Sydorenko, I. G. (Chuiko Institute of Surface Chemistry National Academy of Sciences of Ukraine, 2009)
The electrical oxidation of ascorbic acid at the electrode of carbon nanotubes in phosphate buffer solution has been studied. Due to the presence of oxygen containing functionnal groupes at the ports of nanotubes, they have a catalytic activity in the reaction of ascorbic acid electrical oxidation. The linear dependence of the plateau current of ascorbic acid oxidation on its concentration in the solution is kept within concentration of 0.1 – 10 mmol×dm-3. The presence of citric acid doesn’t interfere with determination of ascorbic acid concentration what gives chance to apply the method for determination of juices antioxidant activity, particularly that of citric fruits.